STRATEGY FOCUSSED IT FACILITATION OF AGRICULTURE EXTENSION SERVICES - THE KISSAN-KERALA APPROACH - K.R. Srivathsan, Ajith Kumar, K. Madhavan Nair, C. Hariprasad (2004)
In this paper we provide an overview of the KISSAN-Kerala project that is jointly developed and managed by the Indian Institute of Information Technology and Management - Kerala, Department of Agriculture of the Kerala Government and the Kerala Agriculture University. It is a project that supports effective IT facilitated extension services where extension officials are backed by specialized groups of agriculture consultants or experts interacting over a Knowledge Management Portal run by the project. This networked consulting is strengthened by building awareness through a mass media television program in Agriculture called Krishi Deepam that is composed and run by the project team. The paper also provides a number of actionable areas and national initiatives that need to be taken up for effective uses of IT facilitated services in Agriculture. These are based upon the concepts developed and experience gained in the KISSAN project. The paper also makes a case for commencing an advanced postgraduate and research institute be commenced at the national level in the area of Applied Information Systems and Management in agriculture.